Kebijakan Pemerintah Mahmoud Ahmadinejad Membangun Kekuatan Militer Iran sebagai Respon terhadap Persepsi Ancaman Israel - Vici Armia Lifanti; Harmiyati Harmiyati (Jurnal Paradigma, 2012)
After Ahmadinejad’s elected as a president, the relationship between Israel and Iran was getting worse. Its caused by Ahmadinejad statements about Israel and his desire to continue the development of Iran’s nuclear facilities. Israel opposed the program because Israel suspect that Iran’s nuclear program will aim to create a nuclear weapon. By the senior official stating, Israel threatened to attack Iran’s nuclear facilities. If Iran still continueing their nuclear program. Israel’s threat was strongly proved with helding military exercise and also buy combat aircraft capable of reaching Iranian territory with one refueling. Iran as a threatened country started trying to build its military force which expected to be used as deterrence against a possible military strike by Israel. The increasing of Iran’s military power also involves cooperation with Rusia, China and North Korea.